Extensive Emphysematous Pyelonephritis in a Nondiabetic Female Cat - Treatment with Unilateral Nephroureterectomy - Kim, Hye-Min; Goh, Yeong-Seok; Kim, Hak-Hyun; Chang, Dong-Woo; Na, Ki-Jeong; Park, Kyung-Mee (Acta Scientiae Veterinariae, 2023)
Background: Emphysematous pyelonephritis (EPN) is an acute, severe necrotizing infection of the renal parenchyma and surrounding tissues that results in gas formation in the kidney, collecting system, or surroundings. EPN is a rare condition in veterinary medicine and occurs most frequently in dogs with diabetes mellitus. Although the prognosis of medical management in animals is poor, the standardized treatment protocol according to EPN severity is unclear. This report describes the first case of a nondiabetic female cat with extensive EPN and good prognosis following direct nephroureterectomy (NU). Case: A 10-year-old spayed female cat presented with the chief complaint of an acute loss of weight within 1 week, vomiting, and disorientation including stumbling, discoordination, circling, wobbling, head tilting, and difficulties in standing. At presentation, the patient had a body condition score of 1/9 and weighed 2.6 kg. Blood examination revealed leukocytosis, anemia, and hypoproteinemia. Abdominal radiography revealed severely decreased serosal details. A massive gas silhouette observed in the peritoneal and retroperitoneal cavities, was diagnosed as abdominal free gas. Abdominal ultrasound showed an accumulation of moderately anechoic fluid mixed with gas and cyst-like capsules around the left kidney. Left partial ureteral obstruction and dilation were also observed. Computed tomography (CT) was performed without sedatives or anesthetic drugs. The findings showed severe inflammatory changes in the peritoneum and a loss of the normal inner structure in the left kidney. A pyelogram of the left kidney was not observed after injection of the contrast material. Diffuse fat stranding and free gas observed in the mesentery of the entire abdominal cavity and around the left kidney were considered septic peritonitis. Urinalysis revealed proteinuria and hematuria. Numerous neutrophils with rod-type bacteria were observed in the ascites. Following diagnostic examinations, the patient was diagnosed with extensive left EPN, including inflammatory ascites and abdominal free gas. Therefore, emergency NU of the nonfunctional left kidney and ruptured ureter and thorough abdominal lavage were conducted. Diffuse inflammation and a nephrolith were observed in the section of the harvested kidney. The nephrolith was composed of 100% calcium oxalate monohydrate. The real-time polymerase chain reaction (RT-PCR) test for feline infectious peritonitis (FIP) was negative. Escherichia coli was detected in the ascites, and antibiotic therapy was administered following the antibiotic sensitivity test. The histological findings from the left kidney and ureter included marked chronic inflammation and fibrosis. The patient was discharged 4 days after surgery. During the 8-month follow-up period, the patient’s condition improved. Discussion: This was a unique case of EPN in a nondiabetic cat and the first reported case of EPN with a ruptured ureter, including abdominal free gas, inflammatory ascites, and peritonitis. This patient had a bacterial urinary tract infection with E. coli, which is the most frequently isolated pathogen in humans. This gas-forming bacteria produced a massive amount of gas and inflammation that were considered to have ruptured the urinary tract, so that the gas was released into the abdomen. This case corresponded to class 3B, with two risk factors according to the human EPN classification system. Direct NU and abdominal lavage were performed as emergency surgeries. The patient stabilized gradually and showed a good prognosis. Immediate surgical intervention is recommended in animal patients showing the extensive EPN stage. Keywords: kidney, nephroureterectomy, emphysematous pyelonephritis, peritonitis, cat, E. coli.